Cognitive reserve and lifestyle. - Scarmeas, Nikolaos; Stern, Yaakov (J Clin Exp Neuropsychol, 2003)
The concept of cognitive reserve (CR) suggests that innate intelligence or aspects of life experience like educational or occupational attainments may supply reserve, in the form of a set of skills or repertoires that allows some people to cope with progressing Alzheimer's disease (AD) pathology better than others. There is epidemiological evidence that lifestyle characterized by engagement in leisure activities of intellectual and social nature is associated with slower cognitive decline in healthy elderly and may reduce the risk of incident dementia. There is also evidence from functional imaging studies that subjects engaging in such leisure activities can clinically tolerate more AD pathology. It is possible that aspects of life experience like engagement in leisure activities may result in functionally more efficient cognitive networks and therefore provide a CR that delays the onset of clinical manifestations of dementia.
Keywords: Adaptation, Physiological; Adaptation, Psychological; Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognition; Cognition Disorders; Educational Status; Exercise; Health Behavior; Humans; Life Style; Middle Aged; Nerve Net; Neuronal Plasticity; Recruitment, Neurophysiological; Risk Factors; Severity of Illness Index